AutoAPI – A Web-Based Tool for Specification of an API Endpoint to Return JSON Data From an XML Source. (20th August 2021) - Moore, Adrian
AutoAPI is a web-based tool for the specification and management of API endpoints to online XML data sources. The APIs generated return the data in JSON format. The tool allows users to specify the field names to be used in the JSON data and to control which elements of the original data set are returned. Options are provided for the returned data to skip null values and to flatten the structure that is retrieved.autoAPI is written in Python/Flask and is available under the MIT licence. The software is available from GitHub ( https://github.com/aamoore/autoAPI ) and can be seen deployed at https://autoapi-app.herokuapp.com/?http://apis.opendatani.gov.uk/translink/3042AA.xml .